The economics of options-implied inflation probability density functions - Yuriy Kitsul; Jonathan H. Wright (The Johns Hopkins University, Department of Economics, 2012)
Recently a market in options based on CPI inflation (inflation caps and floors) has emerged in the US. This paper uses quotes on these derivatives to construct probability densities for inflation. We study how these pdfs respond to news announcements, and find that the implied odds of deflation are sensitive to certain macroeconomic news releases. We compare the option-implied probability densities with those obtained by time series methods, and use this information to construct empirical pricing kernels. The options-implied densities assign considerably more mass to extreme inflation outcomes (either deflation or high inflation) than do their time series counterparts. This yields a U-shaped empirical pricing kernel, with investors having high marginal utility in states of the world characterized by either deflation or high inflation.
Keywords: C22; E31; E44; G12; 330; Inflation; Floors and Caps; Derivatives; Physical measure; Risk-Neutral Measure; Finanzmarkt; Optionsgeschäft; Derivat; Inflation; Berechnung; USA